2008
DOI: 10.14723/tmrsj.33.941
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanochemical Route to Synthesize LiMn<sub>2</sub>O<sub>4</sub> as a Cathode Material for Lithium Batteries

Abstract: Lithium manganate, LiMn 2 0 4 , applicable as a cathode material for lithium batteries has been synthesized by a redox mechanochemistry route. Gamma-Mn0 2 shows an excellent reaction ability with LiOH under grinding and the amorphous ground product can be crystallized to LiMn 2 0 4 at 400°C despite the requisition of the partial reduction of Mn0 2 to MnruMnrv0 5 • Contrary, Mn 2 0 3 shows a poor reactivity. The dissociation of the edge-sharing chains of Mn0 6-octahedra in yand ~-Mn0 2 and the increased reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The powders obtained from PH were smaller than PC; 153, 214 and 399 nm at the same temperatures. As described in a separate paper, 12) the fine powders prepared by the mechanochemical method indicate the excellent cycle performances for the rechargeability.…”
Section: Reduction Ability Of Some Ketones and Alcoholsmentioning
confidence: 78%
See 1 more Smart Citation
“…The powders obtained from PH were smaller than PC; 153, 214 and 399 nm at the same temperatures. As described in a separate paper, 12) the fine powders prepared by the mechanochemical method indicate the excellent cycle performances for the rechargeability.…”
Section: Reduction Ability Of Some Ketones and Alcoholsmentioning
confidence: 78%
“…Mechanochemical process based on the enhanced chemical reactivity of finely ground and activated particles under grinding is expected as one of the candidate synthesis routes of inorganic powders. 1)-3) This process can be successfully applied to the synthesis of titanates, 4)-6) ferrites, 7)-11) manganates, 12) cobaltates, 13) and others. In these applications, the chemical valence (oxidation number) of the available starting materials is sometimes different from that of the desired products.…”
Section: Introductionmentioning
confidence: 99%
“…The MC treatment was conducted at the revolution frequency of 6 s −1 for 3h. For the solvothermal (ST) treatment, 20cm 3 of the mill-treated slurry was charged into the Teflon-lined stain-less steel container (50cm 3 ) and heated at 150 o C for 16h. The products were washed with acetone and dried at 85 o C under vacuum for precursors AHG00 (MC) and AHG15 (MC/ST).…”
Section: Methodsmentioning
confidence: 99%
“…The other is the reduction of particles size, expecting the high surface energy to stabilize surface defects [1]. Mechanochemical process is applicable to the reduction of particle size by promoting the nucleation [2,3]. The authors have been demonstrated the mechanochemical synthesis of LiMn2O4 from LiOH and MnO2, where the amorphous ground products are crystallized above 400 o C and the LiMn2O4 powder with the size of 380 nm shows a certain improvement of the cycle performance.…”
Section: Introductionmentioning
confidence: 99%